The standoff - Hogan, Chuck (New York : Doubleday, 1995)
A nightmare erupts when an FBI negotiator confronts a notorious criminal who has barricaded himself, his wife, and his five children in a secluded mountaintop cabin in Montana. Their tense, nine-day standoff builds into a deadly war of nerves between two unforgettably charismatic and strong-minded protagonists.
Keywords: Criminals -- Montana -- Fiction; Detective and mystery fiction